Every time a colleague mentions spontaneous. Issue 3 (December 2020) - Disney, Dan
Abstract : Extracted from a longer poem in progress provisionally called twentytwenties, 'every time a colleague mentions spontaneous ' is a formally inventive work that is also allusive and sharply biting about various aspects of contemporaneity (among them, 'Reality Apathy', 'Digital Evangelism', 'the Virus', 'the Ends of History') and of present sensibilities.